A lightweight CNWs-SiO2/3Al2O3·2SiO2 porous ceramic with excellent microwave absorption and thermal insulation properties. Issue 12 (15th August 2020) - Dong, Yongpeng; Fan, Xiaomeng; Wei, Hanjun; Hou, Zexin; Li, Minghang; Qu, Qiang; Yin, Xiaowei; Cheng, Laifei; Zhang, Litong
Abstract: To obtain excellent microwave absorption and thermal insulation properties, carbon nanowires reinforced SiO2 /3Al2 O3 ·2SiO2 composite ceramics (CNWs-SiO2 /3Al2 O3 ·2SiO2 ) were fabricated by catalytic chemical vapor deposition (CCVD) using C2 H4 as the carbon source. The content of CNWs in SiO2 /3Al2 O3 ·2SiO2 porous ceramics can be adjusted by controlling the concentration of the catalyst precursor and the CCVD time. A higher concentration of catalyst precursor and longer CCVD time are beneficial for the growth of CNWs and for improving the electromagnetic wave (EMW) absorption properties of CNWs-SiO2 /3Al2 O3 ·2SiO2 . However, CNWs are harmful to impendence matching due to the strong reflection and weak absorption when the content exceeds the threshold (30 wt%) in SiO2 /3Al2 O3 ·2SiO2 porous ceramics. CNWs are also harmful to the thermal insulation properties due to their high thermal conductivity. The results show that CNWs-SiO2 /3Al2 O3 ·2SiO2 can attain good EMW absorption and thermal insulation properties if the content of CNWs is 30 wt% when the concentration of the catalyst precursor is 3 wt% and the CCVD time is 15 min. The effective absorption bandwidth (EAB) can cover from 8.2 to 12.4 GHz (the whole X-band), and the minimum reflection coefficient (RCmin ) is -31 dB at 9.1 GHz. The temperature gradient is 218 °C, which can satisfy the design requirement. Thus, the dielectric and thermal insulation properties are designable for CNWs reinforced SiO2 /3Al2 O3 ·2SiO2 porous ceramics to obtain excellent EMW absorption and thermal insulation properties.